(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The use of instructional resources based on information and communication technology (ICT) by secondary English instructors is examined in this study. We investigate the importance of teachers’ attitudes towards ICT, their self-confidence in utilising these tools, and their competence in incorporating ICT into their teaching practises using a case study method. The data, collected through interviews, observations, and surveys from a sample of English teachers, highlight the complex interplay of these factors and suggest that positive attitudes, high self-confidence, and strong competency are significant predictors of teachers’ willingness and ability to adopt ICT-based instructional materials.